1996
DOI: 10.1016/0014-5793(96)00788-0
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for nickel of the transmembrane translocation of NiFe‐hydrogenase 2 in Escherichia coli

Abstract: The cellular location of membrane-bound NiFehydrogenase 2 (HYD2) from Escherichia coil was studied by immunobiot analysis and by activity staining. Treatment of spheroplasts with trypsin was able to release active HYD2 into the soluble fraction, indicating that HYD2 is attached to the periplasmic side of the cytoplasmic membrane and that HYD2 undergoes a trans-membrane translocation during its biosynthesis. By using a n/k mutant deficient in the high affinity specific nickel transport system, we show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 37 publications
(66 reference statements)
5
33
1
Order By: Relevance
“…Those early studies identified a strong dependence on FNR for hydrogenase 1 and 2 isoenzyme synthesis (Sawers et al, 1985). Later work suggested that the role of FNR was likely to be indirect and was a reflection of its requirement for nickel transport (Wu et al, 1989 ;Rodrigue et al, 1996). The present study demonstrated only a minor involvement of FNR in transcriptional regulation of hya (see also and hyb operon expression, which is in accord with an indirect involvement of the regulator in operon expression.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Those early studies identified a strong dependence on FNR for hydrogenase 1 and 2 isoenzyme synthesis (Sawers et al, 1985). Later work suggested that the role of FNR was likely to be indirect and was a reflection of its requirement for nickel transport (Wu et al, 1989 ;Rodrigue et al, 1996). The present study demonstrated only a minor involvement of FNR in transcriptional regulation of hya (see also and hyb operon expression, which is in accord with an indirect involvement of the regulator in operon expression.…”
Section: Discussionsupporting
confidence: 73%
“…However, the results of a later study (Wu et al, 1989) suggested that the reduced level of both enzymes in the fnr mutant was the consequence of impaired nickel transport. Reduced cytoplasmic nickel precludes processing of either hydrogenase precursor and, as a result, the apoenzymes were enzymically inactive and not targeted to the membrane (Rodrigue et al, 1996). An analysis of the transcriptional regulation of the operons encoding both enzymes would resolve this question unequivocally and at the same time provide key information on the control of enzyme synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Rocket immunoelectrophoresis was performed as described previously (29). Trypsin-catalyzed solubilization of membrane-bound hydrogenase 2 activity from both washed membranes and spheroplasts was performed essentially as described (30,31). Protein concentration was estimated by the method of Lowry et al (32).…”
Section: Tat-dependent Protein Exportmentioning
confidence: 99%
“…In addition, certain Tat precursors associate with other polypeptides in the cytoplasm that do not contain signal peptides. In a process called ''hitchhiker export,'' the two polypeptides form a complex that is targeted to the Tat translocation apparatus and then is exported to the periplasm by virtue of the signal peptide in the precursor (Rodrigue et al 1996). In the absence of the assembly partner or when cofactor assembly has been impaired by mutation, protein export through Tat does not take place (Rodrigue et al 1996;Halbig et al 1999).…”
mentioning
confidence: 99%
“…In a process called ''hitchhiker export,'' the two polypeptides form a complex that is targeted to the Tat translocation apparatus and then is exported to the periplasm by virtue of the signal peptide in the precursor (Rodrigue et al 1996). In the absence of the assembly partner or when cofactor assembly has been impaired by mutation, protein export through Tat does not take place (Rodrigue et al 1996;Halbig et al 1999). These observations together with in vitro and genetic evidence point to a protein folding quality control mechanism that is intrinsic to Tat translocation (DeLisa et al 2003).…”
mentioning
confidence: 99%